PERAN SERIKAT PEKERJA DALAM MENDORONG PRODUKTIVITAS DAN PENINGKATAN KESEJAHTERAAN PARA PEKERJA PADA PT NIPPON SHOKUBAI INDONESIA-CILEGON - Sri Ndaru Arthawati (Tirtayasa Ekonomika, 2018)
Trade unions are organizations that join together to achieve common goals such as wages, hours, and working conditions. The organization can consist of individual workers, professionals, former workers, or unemployed. Over the last 300 years many labor unions have developed into a number of forms and have been influenced by economic and political development. The objectives and activities of trade unions vary. The research method is explanatory, the sample size is 100 respondents, the sampling technique used the model of Partial Least Square (PLS) with t-test by using smart PLS software version 2.0 M3.Trade unions are organizations formed from workers both in companies that are free, open, independent, democratic, and responsible for fighting, defending and protecting the rights and interests of workers and improving the welfare of workers and their families. The results showed that the role of trade unions in promoting productivity and improving the welfare of workers at PT NIPPON SHOKUBAI INDONESIA had a significant variables effect on employee performance.